Characteristics of Viewers' Perceptions of Indonesian League 1 Football Broadcasts with the English Premier League 2021/2022 Season: Karakteristik Persepsi Penonton Terhadap Siaran Sepakbola Liga 1 Indonesia dengan Liga Premier Inggris Musim 2021/2022 - Benidektus Adi Prianto (Institut Teknologi Bandung, 2022)
Professional soccer has grown into a huge industry. It is not only about winning games but also making money. One aspect that must be considered is broadcast quality (service quality), it is important in the marketing process in the football industry, because it will relate to customer loyalty and satisfaction itself. So that with the improvement of broadcast quality will increase loyalty and satisfaction as well as attract more viewers who will contribute to the company's revenue as well as the football club through the results of the distribution of television ratings. This study aims to determine the audience's perception of the Indonesian league 1 soccer broadcast with the 2021/2022 English premier league broadcast which is one of the references for broadcast quality. this descriptive quantitative research involved soccer viewers from all over Indonesia with a sample of (N = 459), using a questionnaire. In this study, it was found that there were significant differences in results between audience perceptions of the Indonesian league 1 broadcast and the English premier league 2021/2022 season. With the best assessment of the Indonesian league 1 soccer broadcast in the visual graphics quality variable with a